Network convergence : - Hanrahan, Hu (John Wiley & Sons Ltd, 2007)
Network Convergence creates a framework to aid the understanding of Next Generation Networks, their potential for supporting new and enhanced applications and their relationships with legacy networks. The book identifies and explains the concepts and principles underlying standards for networks, services and applications.